Mapping Based Quality Metrics for Mesh Deformation Algorithms Using Radial Basis Functions - Changchuan Xie; Sijia Jia; Yingjie Li; Chao An; Chao Yang (Applied Sciences, 2020)
The mesh deformation method based on radial basis functions is widely used in computational fluid dynamics (CFD) simulation with a moving boundary. The traditional method for generating CFD mesh quality metrics called mesh-based metrics use the information of deformed mesh with specific element node coordinates and a connectivity relationship. This paper develops a new mesh quality, metric evaluating method based on the mapping process between the initial and deformed mesh, which is named mapping-based metrics. Mapping-based metrics are evaluated based on the conception of the deformation principle in continuum mechanics. This method provides a new point for mesh quality evaluation without requirements of deformed mesh coordinates and element connectivity information. Three test cases show that, comparing with indirectly solving by a geometrical method, mapping-based metrics accurately reveal the changes of the angle and area over the whole deformed domain. Additionally, the mapping-based metrics give high applicability to the quality of deformed mesh compared to mesh-based metrics. The quality evaluation method for CFD mesh proposed in this paper is effective.